Analisis Pendekatan TaRL Pada Pembelajaran Matematika Materi Piktogram Kelas 2 Sekolah Dasar - Nugraheni, Selviana Vivi; Nuvitalia, Duwi; Purnamasari, Veryliana; Aris Kurnia, Evivalen (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
Education needs to facilitate the characteristics of diverse students. Appropriate learning according to characteristics needs to be adjusted to the learning needs of each student. By paying attention to the learning needs of students, learning will be able to create meaningful concepts for each individual. Therefore, an approach is needed to be able to cover all the diverse learning needs of students. The Teaching at The Right Level (TaRL) approach is a solution choice for effective learning. This study aims to determine the influence of the TaRL approach in grade IIB of SD Bukit Aksara Mathematics subject. This study uses a qualitative descriptive method. The subjects of this study are all students in grade IIB of SD Bukit Aksara. Data collection techniques are carried out by means of observation, interviews, tes and documentation. The results of the study show that the application of the Teaching at The Right Level (TaRL) approach to mathematics subjects which includes mapping students' needs for pictogram material, designing and implementing different learning plans, reflecting and evaluating learning, and designing continuous learning improvements, is able to produce changes in learning outcomes and increase student motivation in learning.